Conductive ink, paste, and conductive polymer composite material having silver nanowires and metal nanoparticles, and a corresponding method.

JP2026534472APending Publication Date: 2026-10-16EKC TECHNOLOGY INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026518626
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-09-27
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

の信頼が与えられる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026534472000001_ABST
    Figure 2026534472000001_ABST
Patent Text Reader

Abstract

A concentrated fluid composition having at least about 45% by weight of total metal is used to form a conductive material. The composition includes metal microparticles, such as silver flakes, silver particles and / or silver nanowires, and in embodiments of particular interest, includes a reducible metal composition such as one or more silver salts. The composition includes an organic precursor that forms a polymer matrix and includes a soluble polymer binder, a crosslinkable or polymerizable monomer, oligomer or polymer, or a mixture thereof. Using the fluid precursor composition, a conductive structure such as a composite of a solid polymer matrix and at least about 45% by weight of metal can be formed. The composite has a density of about 5 × 10 -3 It may have resistivity of Ω·cm or less. Methods for forming fluid precursor compositions and composite materials are described.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] Cross-reference of related applications This application claims priority to the pending U.S. Provisional Patent Application No. 63 / 540,772, filed by Virkar et al. on 27 September 2023, titled "Silver Nanowire Based, Electrically Conductive Inks, Pastes and Electrically Conductive Adhesives and Corresponding Methods," which is incorporated herein by reference.

[0002] This invention relates to conductive composite materials comprising polymers and metal particulates, such as silver nanowires. The invention further relates to supplementing the electrical conductivity of conductive composites by in-situ reduction of silver for the formation of cured composite materials. The invention also relates to methods for forming these composite materials. [Background technology]

[0003] Metal-loaded polymers (e.g., crosslinked polymers) have been found to provide useful alternatives to solder and other metal-only electrical connector materials. Conductive structures can be formed by the deposition of suitable precursor materials, which may be pastes or more fluid inks, and may include, for example, monomers, oligomers, soluble polymers, and their solvent mixtures. Fine particulate metals, such as silver nanoparticles or silver flakes, can be used as metal fillers. While other metals may provide sufficient electrical and thermal conductivity, silver is the most conductive metal. These materials can be conveniently applied in a variety of processing situations. [Overview of the project] [Means for solving the problem]

[0004] In a first aspect, the present invention relates to a fluid precursor composition for forming a conductive material, having at least about 45% by weight of total metal weight relative to the total weight of the composition, and at least about 2% by weight of organic precursor for forming a polymer matrix. The fluid precursor composition can be used to form a conductive material. The composition comprises metal nanoparticles such as silver flakes and / or silver particles, and a reducible metal composition such as one or more silver salts. The metal nanoparticles may also include metal nanowires such as silver nanowires. The composition comprises organic precursors that form a polymer matrix. The precursors may include soluble polymer binders, crosslinkable or polymerizable monomers, oligomers or polymers, or mixtures thereof. For example, the precursors may include one or more monomers, such as (meth)acrylate monomers, hydroxy and / or epoxy-functionalized urethane acrylate monomers, and monomers that form epoxy resins. The precursors may be thermosetting and / or UV-curable.

[0005] In another embodiment, the present invention relates to a fluid precursor composition for forming a conductive structure, comprising an organic precursor of a polymer matrix; metal nanoparticles comprising silver nanowires and non-nanowire metal particles, wherein the metal nanoparticles contain silver nanowires in an amount of about 5 to about 90% by weight relative to the total weight of the metal nanoparticles. The non-nanowire metal particles may include silver flakes, silver particles, or a combination thereof.

[0006] In another embodiment, the present invention relates to a conductive composite material formed from a fluid precursor composition. The composite material comprises a solid polymer matrix and at least about 45 wt% of a metal, the metal comprising a1) a feature formed from metal nanoparticles other than nanowires and b1) a feature formed from silver nanowires, deposited metal from a reducing metal composition, or both; or a2) a structure formed from silver nanowires and b2) deposited metal from a reducing metal composition. The conductive composite material comprises about 5 × 10 -3 It may have a resistivity of Ω·cm or less.

[0007] In another embodiment, the present invention relates to a method for forming a precursor composition for forming a conductive composite material. The method comprises combining a) a polymer matrix precursor containing a crosslinkable polymer precursor, a polymerizable monomer / oligomer, a soluble polymer binder, or a combination thereof, and b) a metal component provided as two or more of 1) metal nanoparticles other than nanowires, 2) silver nanowires, or 3) a reducible metal composition, wherein the precursor composition contains at least about 45% by weight of the total metal in all forms, and the metal is provided as silver nanowires only and as a reducible metal composition, the polymer matrix, following curing, contains at least 2% by weight, and in some embodiments 8.5% by weight, of the polymer matrix precursor composition.

[0008] In another embodiment, the present invention relates to a method for forming a composite material having high electrical conductivity and organic polymer and metallic components. The method comprises curing a deposited composition to manipulate the reduction of silver ions and form a silver metal, wherein the deposited material is a precursor composition comprising a polymer precursor, silver nanoparticles, and a molten silver composition, and the curing comprises applying heat, ultraviolet light, or both for a time sufficient to reduce the silver ions to a silver metal and reduce the resistivity by at least about 25%. [Brief explanation of the drawing]

[0009] [Figure 1] This is a plot of calculated sheet resistance values ​​as a function of sintering time at 250°C for a composite material containing approximately 19 wt% H-nanowires (HNW), approximately 41 wt% silver flakes (AgFL), approximately 14 wt% silver macroparticles (AgMP), and approximately 7 wt% silver trifluoroacetate (AgTFA) in a UV-curable urethane acrylate polymer matrix. [Figure 2] Figure 1 shows a plot of resistivity as a function of sintering time for the composite material described and a similar composite material containing approximately 13% by weight of AgTFA. [Figure 3A-3B]This is a 5x magnification image of the composite material shown in Figure 1, which was coated onto polyester terephthalate (PET), cured, and then subjected to a cross-hatch adhesion test. [Figure 3C] Figure 2 shows a 5x magnification image of a composite material containing 13 wt% AgTFA, which was coated onto PET, cured, and then subjected to a cross-hatch adhesion test. [Figure 4A-4B] This is a 5x magnification image of the composite material shown in Figure 1, after it has been coated onto glass, cured, and then subjected to a cross-hatch adhesion test. [Figure 4C] Figure 2 shows a 5x magnification image of a composite material containing 13 wt% AgTFA, which was coated onto glass, cured, and then subjected to a cross-hatch adhesion test. [Figure 5] Figure 3A is a 5x magnification image showing the adhesive surface of the tape used in the cross-hatch adhesion test of composite materials on PET, as described above. [Figure 6] Figure 4A is a 5x magnification image showing the adhesive surface of the tape used in the cross-hatch adhesion test of composite materials on glass described above. [Figure 7] Figure 1 shows a plot of resistivity as a function of curing energy for the composite material described in Figure 1, which was cured using high-intensity pulsed light (IPL). [Figure 8A] Figure 1 shows an image of the cross-section of the composite material described in Figure 1 at a magnification of 10,000, before the composite material is hardened or sintered. [Figure 8B] Figure 8A shows an image of the cross-section of the composite material described above at a magnification of 20,000 after the composite material has been cured using IPL. [Figure 8C] Figure 8A shows a 10,000x magnification image of the cross-section of the composite material described above, after the composite material has been sintered at 250°C for 15 minutes. [Figure 9A-9B] Figure 1 shows images of the cross-section of the composite material described in Figure 1 at magnifications of 10,000x and 60,000x, respectively, before the composite material is hardened or sintered. [Figure 10A-10B]These are images at 350x magnification and 20,000x magnification respectively of the cross-section of the composite material described with reference to Figure 8A, after the composite material has been cured using IPL. [Figure 11A-11B] These are images at 3,000x magnification and 10,000x magnification respectively of the cross-section of the composite material described with reference to Figure 9A, after the composite material has been sintered at 250°C for 15 minutes. [Figure 12] This is a bar graph showing the specific resistivity of a composite material comprising about 20 wt% HNW, about 44 wt% AgFL, about 15 wt% AgMP, and about 2.5 wt% AgTFA in a UV-curable urethane acrylate polymer matrix. [Figure 13] This is a bar graph showing the specific resistivity of a composite material comprising a combination of about 20 wt% HNW, about 40 to 60 wt% AgFL, about 10 to about 20 wt% AgMP, and about 7 wt% AgTFA in a UV-curable modified acrylate polymer matrix. [Figure 14] This is a bar graph showing the specific resistivity of a composite material comprising a combination of about 20 wt% HNW, about 60 to 80 wt% AgFL, about 5 to about 10 wt% AgTFA, and about 5 to about 10 wt% silver acetate (AgAc) in a thermosetting epoxy polymer matrix. DETAILED DESCRIPTION OF EMBODIMENTS FOR CARRYING OUT THE INVENTION

[0010] It has been found that silver nanowires can further improve the electrical conductivity of metal-loaded polymers and resins with high metal loading, based on their ability to achieve very low resistivity while maintaining desirable properties imparted by the polymer. The effect of silver nanowires may be disproportionate to their mass of silver due to the electrical conduction pathways provided by the nanowire morphology. How to avoid fluidic limitations to obtain high loading of silver nanowires in the solvent and the loaded polymer has been discovered. Combinations of silver nanowires with other metal shapes can adapt the properties of the material while improving electrical conductivity. Furthermore, or alternatively, the use of reducible metal compounds may provide a significant improvement in electrical conductivity based on any of the base metal nanoparticle shapes. While blends with some silver nanowires are desirable, reducible metal salts have been found to be beneficial even when used in composites that do not contain silver nanowires. The reduction in electrical resistivity achieved with reduced silver salts is disproportionate to the amount of deposited metal, thus suggesting some effectively directed metal deposition that is cooperative in establishing conductive pathways through the material. Similarly, silver nanowires may help establish conductive pathways based on their length. A curing process can be used in which the polymer matrix is ​​solidified by polymerization, crosslinking, solvent removal, reduction of silver ions, or a combination thereof. Improved electrical conductivity can provide good processability and simultaneously reduce material usage in high-performance applications such as electronic devices. Very low resistivity is achievable with the composites described herein. Materials can be designed for specific properties desired for particular applications. A wide range of polymer precursors, such as soluble polymers or monomer and / or oligomer resins, can be used. The use of environmentally friendly metals provides a more environmentally harmless alternative to conventional solders for providing electrical connections, or offers other applications such as antistatic agents.

[0011] The properties of the materials described herein will be obvious to those skilled in the art. However, technical terms may not be uniformly adopted in the art. While considerable care has been taken to explain alternative technical terms, this may not be comprehensive and will be appropriately understood by those skilled in the art based on the overall considerations presented herein in the appropriate context.

[0012] The processes described herein involve the formation of a precursor composition to be deposited to form a final conductive structure. Conductive polymer precursor compositions may instead be called inks, pastes, precursor materials, conductive adhesives, or resins loaded with metal particles, although other technical terms may be used in the art for equivalent compositions. The precursor compositions generally have the characteristics of being depositable as coatings, dispersible compositions, printed structures, spreadable pastes, etc., and the rheology of the composition may vary depending on the deposition approach.

[0013] Following the deposition of the precursor composition, the material is cured. As used herein, curing is used broadly to mean the conversion of a fluid material, including a freely pourable and coatable precursor composition, into a solid conductive material, and is not intended to mean a specific chemical reaction unless otherwise described. Thus, as used herein, curing may mean solvent removal, polymerization and / or crosslinking of the precursor composition, reduction of a metal composition, a combination thereof, etc. In some embodiments, the curing process is generally influenced by a process of polymerization and / or crosslinking of the precursor composition. In additional or alternative embodiments, the incorporation of a reducible metal composition may also affect the process conditions. Curing may involve the evaporation of a solvent, with or without heat. Some polymer binders can be used in the precursor composition, the polymer binder is dissolved in a solvent to form the precursor composition, and by removal of the solvent, the polymer binder and composite conductive structure solidify, without necessarily crosslinking the polymer. Polymer binders can also be formed by polymerization during curing, with or without crosslinking, with some crosslinking, or with a high degree of crosslinking. Regarding the crosslinking system, the initial precursor composition may include monomers, oligomers, or polymers, and is soluble or liquid as a non-volatile solvent. The polymer can be cured by heat (thermal crosslinking), radiation (UV-induced crosslinking), or simply by solvent evaporation. The system may also include various photoinitiators or thermal initiators, adhesion enhancers, rheological modifiers, reducing agents, and other additives that promote crosslinking. Reduction of metal compounds may occur in conjunction with polymer crosslinking or as a result of a separate treatment.

[0014] The resulting cured material is a solid in which metal is embedded within a polymer matrix. The composition may be selected for appropriate adhesion to the intended structure. The polymer matrix can generally provide the desired cohesion with appropriate metal loading, which can be high loading and suitable processing, thereby achieving appropriate uniformity. In some embodiments, other organic materials different from the polymer matrix may also be used for deposition, but may remain in the final solid structure or be removed by subsequent processing. The metal loading may be adjusted to achieve the desired electrical conductivity, with possible trade-offs with material properties.

[0015] As demonstrated herein, the inclusion of significant amounts of reducible metal compositions, such as silver salts and composites, can be highly effective in improving the electrical conductivity of the resulting conductive structures. Metal species can be reduced by functional groups in the material, forming elemental metal deposits throughout the material. Specifically, solvents, solid organic components, and / or dissolving reducing agents can reduce metal ions / complexes. Based on the nucleation of metal deposits around metal nanoparticles in composites, the deposited metals can form robust electrical conduction pathways. Similar to the applicant's previous research, the reduction and deposition of elemental metals can dramatically improve conductivity by reducing resistance between metal nanostructures and microstructures.

[0016] The solvent in the precursor composition may be volatile and / or non-volatile. In particular, polymer precursors, which are potentially viscous but generally liquid, can function as non-volatile solvents and can be used to disperse metal nanoparticles, including silver nanowires, and the non-volatile solvent may be the polymer precursor. If the reducible metal compound is soluble in the polymer precursor, the precursor composition may not contain any volatile solvents. Any volatile solvent should be compatible with the polymer precursor, meaning that the polymer precursor is soluble in the volatile solvent. While volatile solvents may be desirable as processing aids to adjust viscosity, facilitate blending, allow concentration from evaporation before curing, delay the curing of the resin until the solvent evaporates, or enable other desirable functions, the presence of volatile solvents may be undesirable from an environmental and / or health and / or processing standpoint. In some embodiments, viscous, relatively high boiling point, volatile solvents, such as glycol oligomers and their derivatives, may be used, resulting in the removal of the volatile solvent occurring substantially during curing. This solvent can be used not only to adjust the rheology and subsequent processing of inks or pastes, but also to act as an effective reducing agent for reducing metal ions and complexes. For example, the use of solvents with higher boiling points, above about 125°C, makes it possible to completely reduce metal compounds before the solvent completely evaporates. However, although not bound by theory, the presence of solid metal particles reduces the energy barrier to nucleation and reduction, and therefore heterogeneous nucleation and reduction of reducible metal compounds can occur at lower temperatures (less energy) than in isolated or homogeneous systems without solid metal particles. Thus, even solvents with fairly low boiling points can reduce reducible metal compounds, but these solvents, such as ethanol or isopropanol, may be too volatile for some practical applications depending on the components of other precursor compositions.

[0017] In some embodiments, the conductive composite material does not contain a significant amount of nanowires in the collection of metal nanoparticles, but it is desirable to include silver nanowires to improve electrical conductivity. Nanowires can also improve other properties such as flexibility and stretchability. The ability to achieve high loading of silver nanowires in a good dispersion provides the basis for the silver nanowire-based composite materials described herein. Blends of other silver nanoparticles allow for desirable control of the properties of the loaded resin material before crosslinking and / or drying. Electrical conductivity was improved by the use of silver nanowires. The use of reducible metal compositions may further provide improved electrical conductivity for the deposition of metal and formation of a conductive network that increases the initial metal nanoparticles. Existing products such as conductive adhesives or other metal-loaded conductive resins are generally based on silver micro or nanoparticles and / or silver flakes, forming highly conductive adhesive products. This study provides a significant advance over the applicant's previous research, which has several transformed aspects of silver nanowire processing and provides different studies, including focusing on silver nanoparticles and / or silver flakes. An advance may be considered as introducing a certain amount of silver nanowire to improve the conductive pathways in composite materials and / or to deposit silver or other metals through the composite material via the reduction of metal species, and these mechanisms may provide a significant reduction in electrical resistance.

[0018] Much of the research related to silver nanowires has been directed towards transparent conductive films, and silver nanowire morphology offers significant advantages in forming these structures. The applicant has developed proprietary fusing techniques that provide high-quality transparent conductive films in the art having low sheet resistance, high transmittance, and very low cloudiness. See, for example, U.S. Patent No. 10,029,916 by Virkar et al., entitled "Metal Nanowire Networks and Transparent Conductive Material," and U.S. Patent No. 10,020,807 by Virkar et al., entitled "Fused Metal Nanostructured Networks, Fusing Solutions With Reducing Agents and Methods for Forming Metal Networks," both of which are incorporated herein by reference. In the context of opaque conductive materials, silver nanowires can be loaded into polymers such as adhesives to form conductive fillers. For example, see U.S. Patent Application Publication No. 2024 / 0290516 (hereinafter referred to as the '516 application) by Virkar et al., entitled “Silver Nanowire and Noble-Metal Coated Silver Nanowire Conductive Polymer Composites With Low Loading Percolation Conduction.”

[0019] Recently, the applicant has expanded this study to provide a room-temperature treatment of its proprietary fusion process for metal loading, ranging from highly transparent to semi-transparent and nearly opaque states. This study is shown in U.S. Patent Application Publication No. 2023 / 0416552 by Yang et al., titled "Formation of Electrically Conductive Layers at Room Temperature Using Silver Nanoparticulate Processing and Inks for Forming the Layers," and U.S. Patent Application Publication No. 2024 / 0257991 by Yang et al., titled "Formation of Electrically Conductive Layers at Near Ambient Temperature Using Silver Nanoparticulate Processing and Inks for Forming the Layers," both of which are incorporated herein by reference.

[0020] In the context of opaque conductive structures formed from silver nanoparticles, Professor Magdassi and collaborators were involved in the chemical fusion of silver nanoparticles in relatively thick structures, on the order of micron thickness, to form small but opaque conductive traces. This research is described, for example, in U.S. Patent Application Publication No. 2012 / 0168684 by Magdassi et al., titled "Process for Sintering Nanoparticles at Low Temperature," which is incorporated herein by reference. Magdassi found a significant dependence of the substrate material on the resulting resistivity. Although polymer dispersants are referenced in this context without sufficient detail to explain this aspect of Magdassi's research, Magdassi's samples were formed without the use of a polymer or resin matrix. The absence of a polymer matrix is ​​expected to have different process characteristics, and the fusion mechanism used by Magdassi does not appear to be consistent with the significant use of a polymer matrix.

[0021] The use of silver nanoflakes to form conductive pastes is described for low-temperature processing. These results are described in U.S. Patent No. 11,084,950 by Graddy, Jr. et al., titled “Fast Conductivity Polymer Silver,” which is incorporated herein by reference. Patent '950 describes a resin-containing material. An exemplary conductive material in Patent '950 contains 82.5% by weight of silver flakes. Patent '950 describes a volume of 1 cm³. 3 While the resistance values ​​of samples containing the material have been reported, it appears that sufficient information is not provided to determine the resistivity or to enable the extraction of the resistivity. The material of the '950 patent may be considered essentially a comparative material to the material described herein, having silver nanowire components and / or metal salts.

[0022] Conductive pastes having silver flakes capable of achieving low resistivity are described. For example, see U.S. Patent Application Publication 2015 / 0262728 by Ogiwara et al., entitled "Electrically Conductive Paste Composition and Method of Forming an Electrical Circuit on a Polymer Substrate," which is incorporated herein by reference. This reference teaches a treatment with 87–95% by weight of silver flakes and a temperature of 120°C for 30 minutes. These materials have a higher silver loading than the materials in the '950 patent, but involve heating to cure the material.

[0023] Previous studies involving the loading of silver nanowires into resins have shown remarkably high resistivity for the high-loading materials described above, but have involved fairly low loading of nanowires with the aim of reaching the percolation threshold to achieve some useful electrical conductivity. The applicant found that the use of noble metal-coated silver nanowires succeeded in reducing resistivity at very low loading in certain composites, and that a corresponding improvement could be achieved in the resulting electrical conductivity. See application 516 above. Nevertheless, the electrical resistivity was remarkably lower than the resistances described herein.

[0024] An example of high-loading thermal sintering for forming highly conductive materials is found in Zhang et al., “Electrically Conductive Adhesives with Sintered Silver Nanowires,” 2009 International Conference on Electronic Packaging Technology & High Density Packaging (ICEPT-HDP) 978-1-4244-4659-9 / 09 (2009), incorporated herein by reference. The nanowires were not sufficiently dispersed before the materials were blended to form a composite. Low resistivity values ​​could be achieved. Another procedure, involving the directed blending of silver nanowires into a polymer resin, is described in Wan et al., “A Comprehensive Study of Silver Nanowires Filled Electrically Conductive Adhesives,” J Mater Sci:Mater Electron, DOI 10.1007 / s10854-015-3446-9 (July 2015), incorporated herein by reference. While these illustrative studies likely demonstrated the feasibility of low resistivity-load polymer composites, the processing approaches did not appear likely to contribute to commercial processing.

[0025] The current advances are built upon the applicant's discovery of a technique for forming good dispersions containing high-loading nanowires in a selected solvent, and upon the applicant's earlier research on improving the resistivity of transparent conductive materials by reduction of reducible metal compositions. This high-loading research is described in the pending U.S. Patent Application No. 18 / 634,300 (hereinafter referred to as the '300 application) by Virkar et al., titled "High Loadings of Silver Nanowires: Dispersions and Conductive Pastes; And Corresponding Methods," which is incorporated herein by reference. The ability to form nanowires at high concentrations that are well dispersed in a selected solvent provides strong process versatility for the design of conductive adhesives, pastes, inks, and conductive load polymers in general (collectively referred to as ECAs for convenience). Using well-dispersed silver nanowires, a uniform blend can be produced for inks for depositing ECAs using the desired deposition approach. The '300 application also describes the rheological dependence of silver nanowire morphology. While thin, long nanowires are particularly desirable for transparent conductive films, these long, thin nanowires have a morphology that limits loading because their viscosity increases rapidly as the concentration increases. Therefore, the use of shorter, thicker silver nanowires allows for high loading while maintaining reasonable viscosity.

[0026] High loading allows for the production of even shorter, thicker (lower aspect ratio) silver nanowires, resulting in high-loading, unprocessable materials that may still be at concentrations lower than those desired for specific applications. Furthermore, silver nanowires can be more expensive than other silver forms. Nevertheless, high concentrations of silver nanowires can be brought to processing at appropriate concentrations, and solvents can be removed at various processing stages if necessary. In the study of the present invention, components containing other metals can also be used, but silver nanowires are combined with other silver nanoparticles suitable for ECA formation, particularly silver particles and / or silver flakes. Nanowires may be present in amounts of metal such as silver, about 1 to about 95% by weight relative to the total metal amount. As part of the total hardened solid, the metal can generally be about 45 to about 98%. In further embodiments, all of the metal nanoparticles may be nanowires, i.e., 100%, but due to inclusions of other metal forms, this embodiment effectively includes 95 to 100% by weight of nanowires as a function of the metal nanoparticles in the precursor composition. Those skilled in the art will recognize that a further range within these clear ratios is intended and is contained within this disclosure. With respect to other metal nanoparticles, relative quantities, shapes, and sizes can be selected to provide desired properties and costs. Highly loaded ECA can be cured into materials having low resistivity. It has been found that inclusion of silver nanowires reduces resistivity compared to equivalent ECA without silver nanowires. While specific resistivity reported in the art may depend on the specific polymer matrix, substrate, treatment, and possibly other parameters, the reliability of the beneficial effect of silver nanowire inclusion is given by directly comparing equivalent systems.

[0027] The applicant has developed a unique fusion technique to improve the conductivity properties of transparent conductive films without impairing their optical properties. Patents related to the fusion technique are referenced above. In particular, for the embodiments to be discussed, the fusion technique is based on the inclusion of a reducible metal compound (such as a silver composition), and the reduction of that metal compound can form a fused metal nanostructured network, resulting in a highly desirable structure of transparent conductive films with reduced or eliminated junction resistance while maintaining high flexibility and stability. This fusion process of transparent conductive films is understood as a thermodynamically induced maturation and / or reduction process in which silver deposition is directed towards junctions, lowering the total free energy. As described herein, the reducible silver composition may also promote increased electrical conductivity in the context of high metal loading, low resistivity materials. Similarly, although not constrained by theory, reduction of the silver composition is expected in voids and in the region of low chemical potential between nanostructures and microstructures, as these locations would be thermodynamically favorable. Further reduction of metals helps to better link nanostructures and microstructures such as nanowires, flakes, and microparticles and nanoparticles, thus resulting in better electrical connectivity throughout the structure and lower total resistivity of the entire metal content. The ability to reduce the metal content for a target resistivity improves the range of achievable material properties.

[0028] In the context of the present invention, it has been found that the inclusion and reduction of a reducible metal composition, particularly a silver composition, can lower the electrical resistivity without significantly affecting the workability of the material. Even with high metal loading in the composition, additional filling with situ-reduced metal can be significantly beneficial. From current observations, it is suggested that the reduction in electrical resistance reaches a maximum as the amount of reducible silver composition increases, but in addition to the final hardening and treatment, this may also be a strong function of the overall composition, including the selection and ratio of fillers and the chemistry of the reducible metal composition. The beneficial effect of the reducing metal composition can be confirmed whether or not silver nanowires are present, and although silver nanowires may be the only metal nanoparticles, they still benefit from the use of the reducible metal composition.

[0029] Remarkable properties have been observed with respect to high-loading dispersions of silver nanowires. See the '300 application mentioned above. Firstly, there is a very strong rheological dependence on the shape and size of the silver nanowires. Thinner, longer silver nanowires can exhibit paste-like, non-Newtonian behavior at relatively low wt% concentrations, and the material forms a homogeneous material with no separation observed, even at remarkably low solid volume% concentrations. By using shorter, thicker nanowires, a material with a higher silver nanowire concentration is formed. In this previous study described in the '300 application, the amount of organic polymer dispersant was remarkably low, possibly less than about 20 wt% relative to the weight of the nanowires. Polyvinylpyrrolidone (PVP) is commonly used in nanowire synthesis, and generally, further processing of the nanowires introduces PVP, or related polymers such as copolymers, into subsequent processing. PVP bound to the nanowires can provide dispersibility, and excess PVP can be purified together with the nanowires. Excess PVP not bound to the nanowire surface can be removed by additional purification work. In the context of the present invention for the formation of composite materials, a polymer dispersant such as PVP for silver nanowires can function as a dissolving binder that forms a solid upon removal of the solvent. Therefore, the polymer dispersant for nanowires may be the sole or principal organic component of the conductive composite composition product.

[0030] Silver nanowires generally have a single-crystal structure with very high electrical conductivity along the nanowire, and high metal loading and / or Nano Glue™ are used to reduce junction resistance. The research of the present invention extends to the use of nanowires in composite materials with low loading of silver nanowires having other silver structures of other shapes, replacing a significant portion of silver nanowires and / or supplementing silver nanowires to achieve high metal loading levels. Other suitable metal particle shapes include, for example, silver particles (nearly spherical), silver flakes, other small particulate shapes or mixtures thereof. The relative ratio of silver nanowires to other metal nanoparticles may be selected based on performance issues of the curing material, cost, processing issues, properties of the ECA precursor ink or other issues.

[0031] Composition - Precursor and Cured Conductive Material Regarding the composition, precursor compositions and conductive product materials can be considered. The total weight of metal and organic components may not change significantly to the extent that volatile solvents are absent. During curing, reducible metals may be reduced to elemental metals, polymer precursors (monomers, oligomers, dissolved polymer binders, i.e., resin systems) may be crosslinked into a unitary material, and by solvent removal, a pre-dissolved binder polymer may solidify from the precursor composition. Small amounts of volatile by-product compounds may be generated in the crosslinking process, but this effect is generally not significant with respect to a significant change in the relative ratio of metal to organic. In the relevant embodiments, the crosslinked polymer, a physically or chemically crosslinked polymer, may be considered as a cohesive unitary mass. If a considerable amount of reducible metal composition is present, the metal loaded following reduction during curing may form a unitary mass that intertwines with the crosslinked polymer as a cohesive composite structure. As a result of these processes, a significant difference between the precursor material and the cured material may be that the individual components of the precursor composition lose their individual identity to varying degrees. It is difficult to fully evaluate this, and while the crosslinking density of the polymer or binder polymer entanglement is generally understood as appropriate, the details may change in the case of high metal loading. In some embodiments, after reducing the reducible metal composition, uncrosslinked organic substances may also be removed by further treatment, such as dissolving the organic material. Generally, all or most of the organic contribution can be removed, for example, by using higher temperatures or ablation.

[0032] The precursor composition generally contains metallic and organic components. Where the total metal mass is expressed as a percentage of the precursor composition, as described herein, the total metal mass, such as silver nanoparticles in the precursor composition, can range from an upper limit of about 98% by weight or less, 95% by weight or less in a further embodiment, about 92% by weight or less in some embodiments, about 90% by weight or less in additional embodiments, and about 85% by weight or less in some embodiments, to a lower limit of at least about 50% by weight in some embodiments, about 55% by weight in a further embodiment, about 57.5% by weight in additional embodiments, about 60% by weight in other embodiments, and about 65% by weight in some embodiments. Therefore, a range is described based on either these upper or lower limits, such as about 55% to about 98% by weight. The total metal mass may include metallic nanoparticles and, optionally, reducible metal ions provided as a reducible metal composition. A range of reducible metal compositions is provided below. In some embodiments, the metal nanoparticles contain silver nanowires in proportion to the metal nanoparticles, about 1 to about 95% by weight, about 5 to about 90% by weight in further embodiments, about 10 to about 90% by weight in some embodiments, and about 20 to about 85% by weight in other embodiments; in additional embodiments, all of the metal nanoparticles may be silver nanowires (95 to 100% by weight); and other ranges are based on any selected lower limit range, along with any selected upper limit range of any of these ranges. In additional embodiments, the composite material is formed mainly from non-nanowire nanoparticles, with silver nanowires complementing the material and further contributing to electrical conductivity. For these embodiments, the metal nanoparticles contain silver nanowires in proportion to the metal nanoparticles, about 1 to about 45% by weight, about 2 to about 40% by weight in further embodiments, about 3.5 to about 35% by weight in some embodiments, and about 5 to about 30% by weight in additional embodiments. Contributions from reducible silver salts are shown below. It will be recognized by those skilled in the art that an additional range of total metal mass and silver nanowire proportion of metal nanoparticles, within the clearly defined range described above, is intended and is within the scope of this disclosure.

[0033] The entire precursor composition generally contains about 2 to about 80% by weight of organic components, such as a volatile solvent and polymer matrix precursors, e.g., monomers, oligomers, soluble binder polymers, and / or crosslinkable resins. In some embodiments, the precursor composition may contain from a lower limit of about 2% by weight, about 5% by weight in a further embodiment, about 7% by weight in an additional embodiment, about 8.5% by weight in some embodiments, about 10% by weight in other embodiments, and about 15% by weight in further embodiments, to an upper limit of about 80% by weight, about 70% by weight in a further embodiment, about 60% by weight in an additional embodiment, and about 50% by weight in some embodiments, with the resulting range extending from any designated lower limit to any designated upper limit. The organic components of the precursor composition can be considered to include non-volatile and volatile components. Some polymer components may be volatile until polymerization or crosslinking occurs, but these components may be considered non-volatile if their boiling points are high enough to be converted into non-volatile polymer compositions under process conditions before significant volatilization occurs. During curing, volatile components are generally expected to evaporate, although some may remain bound to the material. Precursor compositions contain little to no volatile solvents, such as residual solvents from the process, and in some embodiments, this is desirable to maintain additional volatile solvents in the precursor composition as processing aids. Generally, polymer precursors can act as non-volatile solvents. Therefore, in some embodiments, the precursor composition may contain volatile solvents in amounts of about 40% by weight or less, about 1 to about 35% by weight in some embodiments, about 3 to about 30% by weight in further embodiments, and about 5 to about 25% by weight in additional embodiments, and any range includes any of these upper limits together with any one of the lower limits. Accordingly, the precursor composition may contain non-volatile organic components in amounts of about 2 to about 55% by weight, about 4 to about 50% by weight in further embodiments, about 5 to about 45% by weight in some embodiments, and about 7 to about 40% by weight in additional embodiments, and the range includes combining any of the upper limits with any of the lower limits of these ranges.The precursor composition generally contains up to about 10% by weight of (optional) processing aids, such as crosslinking agents, viscosity modifiers, plasticizers, curing agents (copolymer components), surfactants, etc., in some embodiments about 0.05 to about 8% by weight, and in further embodiments about 0.1 to about 5% by weight. The remainder of the precursor composition generally contains a metal component. The metal component includes silver nanowires, other metal nanoparticles, and optionally a reducible metal composition. Particularly in embodiments using a reducible metal salt, the solvent, precursor resin, or the resulting polymer matrix generally has hydroxyl groups or other functional groups suitable for reducing the metal species. Furthermore, a reducing agent may be intentionally added to reduce the reducible metal composition. Suitable reducing agents include, for example, ammonium salts or other salts of oxidizable anions, such as sulfites, hydrosulfites, thiosulfites, phosphates, hydrogen phosphates, oxalates, tartrates, formic acid, N,N-dimethylformamide, alcohols, phenolic compounds, such as phenol, aminophenol, metol, hydroquinone, pyrogallol, catechol, 4-amino-3-hydroxy-1-naphthalenesulfonic acid, etc.; polyols such as sugar alcohols; sugars such as monosaccharides and disaccharides; hydroxylamines and their derivatives; aldehydes; hydroxycarbonyl compounds, such as benzoin, froin, and hydroxyketones such as hydroxyacetone; hydrazide derivatives, such as phthalhydrazide, adipic acid dihydrazide, phenidone, etc.; reduced aromatic compounds, such as 1-methyl-1,4-cyclohexadiene, dihydrodaidzein, etc.; and combinations thereof. The amount of reducing agent may be selected based on the molar amount of the metal salt to be reduced based on its equivalent.

[0034] With respect to the relative amounts of materials in the cured composition, the total weight changes due to the loss of any volatile components, and the relative amounts can then be calculated taking into account any combination resulting from the curing process described above, such as the total amount of metal, the total amount of organic, and any separately identifiable components. It will be recognized by those skilled in the art that an additional range of organic concentrations within the above-mentioned clear range is intended and falls within this disclosure.

[0035] The total non-volatile organic content of the conductive solid material product after removal of volatile substances and curing, including products from polymer precursors and any residual processing aids, is about 55% by weight or less. Generally, the conductive solid material product contains about 3 to about 50% by weight of organic components, about 5 to about 45% by weight in some embodiments, about 7 to about 40% by weight in further embodiments, and about 8 to about 35% by weight in additional embodiments, and the range is based on any lower limit range specified together with a specified upper limit range. Its weight percentage value is small compared to the metallic component, but the organic content is relatively large in terms of volume percentage due to the high density of the metallic component. Generally, the ECA composition has a volume percentage of organic components of about 85% by volume or less, about 10 to about 80% by volume in some embodiments, about 15 to about 77.5% by volume in further embodiments, and about 20 to about 75% by volume in additional embodiments, and the range is based on any lower limit range specified together with a specified upper limit range. Even with a significant volume content of organic components, good electrical conductivity can be achieved. Those skilled in the art will recognize that the extent of additional organic contributions within the clearly defined scope described above is intended and falls within the scope of this disclosure.

[0036] To provide the desired contribution to electrical conductivity, the stable nanowires may generally have an average aspect ratio of at least about 10, but in some embodiments, it is preferable to use silver nanowires having an aspect ratio of at least about 50. In further embodiments, the silver nanowires may have an aspect ratio of about 20 to about 3000, about 30 to about 1500 in some embodiments, about 50 to about 1000 in further embodiments, and about 60 to about 500 in additional embodiments, or other ranges of aspect ratios based on any lower limit specified together with any upper limit. The average diameter of the silver nanowires may generally be in the range of about 15 to about 250 nm, about 20 to about 200 nm in further embodiments, about 25 to about 150 nm in some embodiments, and about 30 to about 100 nm in additional embodiments, and a range based on any lower limit range together with any upper limit range. The average length of silver nanowires may range from approximately 1 to approximately 1000 microns, from approximately 2 to approximately 800 microns in further embodiments, from approximately 3 to approximately 700 microns in some embodiments, and from approximately 4 to approximately 500 microns in additional embodiments, and may be based on any of the specified lower and upper limit ranges. Additional ranges of aspect ratio, average diameter, or average length within specific ranges are intended and will be recognized by those skilled in the art as being within this disclosure. The synthesis of thin nanowires with a high aspect ratio and high degree of uniformity is described in U.S. Patent No. 10,714,230 by Hu et al., titled "Thin and Uniform Silver Nanowires, Methods of Synthesis and Transparent Conductive Films Formed From the Nanowires," which is incorporated herein by reference. The formation of thicker and shorter (lower aspect ratio) silver nanowires is described in the '300 application. Silver nanowires with a thin coating of noble metal can be formed to have particularly robust metallic nanowires that are resistant to environmental attacks.The applicant has developed an extensible synthetic approach described in U.S. Patent No. 9,530,534B2 by Hu et al., titled "Transparent Conductive Films," which is incorporated herein by reference. These precious metal-coated silver nanowires are used in the same way as silver nanowires in the formation of transparent conductive coatings. The precious metal-coated silver nanowires should function equivalently to the silver nanowires for the formation of high metal-loading ECAs described herein. The precious metal coating should be relevant to the dimensions of any silver nanowire, and the precious metal-coated silver nanowires are considered to be the silver nanowires described herein.

[0037] In appropriate embodiments, other metal nanoparticles, such as silver nanoparticles other than silver nanowires, may have any reasonable shape, but specific nanoparticles are commercially available for use in polymers, adhesives, or resins to be loaded. In particular, nearly spherical metal flakes and particles offer convenient availability for industrial-scale production at a reasonable cost. Nearly spherical silver nanoparticles are commercially available in nanoscale sizes, with average particle sizes of approximately 200 nm or less, and from small average particle sizes of approximately 10 nm to large average particle sizes of 200–300 nm. Nearly spherical particles of micron size are also commercially available, with average particle sizes of approximately 1 to approximately 100 microns. A reasonable balance of performance and cost may be achievable with average particle sizes of approximately 100 nm to approximately 10 microns. Suitable suppliers of silver particles (micron-sized particles or nanoparticles) include, for example, Heraeus, Inframat Advanced Materials, Ames Goldsmith, Sigma Aldrich, SS Nano, Cerion Nanomaterials, SkySpring Nanomaterials, and Nanocomposix. Silver flakes may have a thin thickness and a length on a micron scale (equal diameter), for example, an average diameter of about 1 to about 20 microns and an average thickness of about 100 nm to about 2 microns. For a typical description of silver nanoflakes, see, for example, U.S. Patent Application Publication 2016 / 0114390 by Hori et al., titled "Flake-Like Silver Powder, Conductive Paste, and Method for Producing Flake-Like Silver Powder," which is incorporated herein by reference. Silver flakes are available from, for example, Tanaka, Ferro, Reade, and Inframat Advanced Materials. In principle, any suitable conductive nanoparticles, or blends thereof, such as silver-coated particles, copper nanoparticles, or nickel nanoparticles, can be used.

[0038] In general, the relative amount of silver flakes to silver nanoparticles or other silver particle shapes can be selected as desired from 1% by weight to 99% by weight, respectively, within this range. This selection may be based on cost, properties and deliverability of the precursor composition, target curing material properties, and / or other selected parameters. For example, thinner deposits may be more favorable to silver nanoparticles than silver flakes. The relative amount of silver nanowires to other silver particle shapes may be similarly affected. As described above, some embodiments may not contain silver nanowires. However, in embodiments of particular interest, the material contains silver nanowires. The above ranges are shown relative to the total metallic component in the precursor composition, and the ranges of silver nanowires as a percentage of the total metallic content and the range of the contribution of reducible metal ions to the total metallic content are shown below. For any of the values ​​in these ranges, non-nanowire silver particles include the remainder of the metallic component, and the values ​​and ranges of non-nanowire silver particles as a percentage of the total metallic content and the total precursor composition follow accordingly.

[0039] With regard to the relevant embodiments, soluble, reducible metal compositions, such as soluble silver compositions, can, in principle, be blended into ECA. The applicant has found that silver fluoride is particularly susceptible to reduction in composite material systems. This is useful for forming transparent conductive films and can be processed at room temperature. See application 552 above. In these systems with high metal loading and low solvent content, silver fluoride reacts too quickly, but if desired, process modifications can be applied to stabilize these metal compositions in the precursor composition. Furthermore, it is possible to change the reactivity of silver fluoride by selecting other chemicals and complexes. Exemplary reducible metal compositions herein are silver acetate, silver trifluoroacetate, and silver heptafluorobutyrate. Suitable reducible silver compositions include, for example, silver acetate (Ag(O2CCH3)), silver trifluoroacetate (Ag(O2CCF3)), silver heptafluorobutyrate (Ag(O2CC3F7)), silver lactate (Ag(O2CCH(OH)CH3)), silver hexafluoroantimonate (AgSbF6), silver fluoride (AgF), silver tetrafluoroborate (AgBF4), silver nitrate (AgNO3), silver perchlorate (AgClO4), silver hexafluorophosphate (AgPF6), or mixtures thereof, which are generally soluble in the target solvent. Process conditions may be influenced by the selection of a specific silver salt. While silver provides a highly conductive deposit through the material, copper, platinum, gold, and other metal compositions can be used as desired. The desirable effect of soluble silver compositions can even be useful in ECAs that do not contain nanowires.

[0040] As described above, silver ions can be considered part of the metallic component of the composite material. The associated anions may form volatile or non-volatile components during curing, and may or may not evaporate accordingly. Generally, the precursor composition may contain silver salts or other reducible metal salts, and the metal / silver weight ratio of reducible metal ions to silver particles such as silver nanowires is generally about 50% by weight or less of silver nanowires relative to the total metal weight, about 0.5 to about 40% by weight in some embodiments, about 0.75 to about 30% by weight in further embodiments, and about 1.0 to about 25% by weight in other embodiments. The total salt weight varies depending on the weight of anions relative to metal cations. Similarly, the weight of metal ions relative to either the entire precursor composition or the cured material can be directly understood from the proportion of total metal, and the reduced metal ions in the composition or material can be easily evaluated accordingly. The metal salts should be soluble in the solvent or precursor mixture, and the concentration of silver or other metal salts is relatively high for large silver nanowire loading. Those skilled in the art will recognize that additional ranges of component concentrations and relative weights within the clearly defined ranges described above are intended and are within the scope of this disclosure. As can be seen in the examples, a significant reduction in resistivity has been achieved using soluble metal compositions combined with commercially available metal pastes. Thus, the use of reducible metal compositions may represent a significant advance independent of the inclusion of silver nanowires.

[0041] The precursors of the final composite polymer, which may be called resins, monomers, oligomers, adhesives, adhesive resins, polymer binders, or other appropriate technical terms, can generally be crosslinked or polymerized by curing during processing. In some embodiments, the precursor is essentially a dissolved binder polymer that is physically crosslinked following solvent removal. With respect to the relevant embodiments, the crosslinking mechanism is generally not limited. For example, crosslinking may be induced by radiation such as ultraviolet light, thermally induced by appropriate heating, spontaneously by solvent removal, chemically by exposure to moisture, or by other reasonable mechanisms. As used herein, polymer precursor broadly refers to resins, adhesives, etc., before curing, such that the polymer precursor is fluid and processable, and possibly viscous, although the terms resin or adhesive may have specific meanings in the narrower fields in which they are used. The synthesis of silver nanowires generally produces polyvinylpyrrolidone (PVP) that is carried over with the silver nanowires. While the amount of PVP can be reduced by further purification, conventional purification results in PVP being approximately 1 to 25% by weight relative to the weight of the silver nanowires, and the PVP carried over with the silver nanowires can be considered a component of the total organic components. Unless otherwise specified, references to polymer components are necessarily interpreted broadly. A wide variety of commercially available adhesives, resins, or other curable polymer precursors are suitable and can be effective as adhesives, broadly defined as polymers suitable for bonding two surfaces to each other. Generally, suitable resins include, for example, acrylates, epoxys, silicones, such as polydimethylsiloxane (considered organic even if it has an inorganic main chain), urethanes, polyvinyl acetals, polyvinyl acrylates, their copolymers, and mixtures thereof. Generally, many crosslinkable resins contain functional groups that can reduce metal ions, or the crosslinking of the polymer forms suitable functional groups. Non-crosslinkable polymers can function as binders in a process that involves dissolving a binder polymer, along with the subsequent removal of the solvent for solidifying the polymer. Due to the high loading of metals in the composite material, the reducing agent may or may not direct all or most of the reduction to specific low-energy locations in the metal structure in order to achieve a confirmed improvement in electrical conductivity.Nevertheless, nucleation of deposits can occur near metallic particles and contribute to the conductive mass.

[0042] In contrast to the solid organic compositions referenced above, the term "solvent" as used herein means a liquid composition at room temperature. The process of dispersing silver nanowires may begin with an initial dispersion in a low-boiling point solvent, after which the dispersion can be maintained in the low-boiling point solvent, but may also include introduction to a higher-boiling point solvent if desired. While the introduction of the solvent is to a higher-boiling point solvent, this relationship is not particularly limited to the introduction solvent, as the initial solvent may be treated under cold or high-pressure conditions. With respect to the initial solvent, the solvent should be suitable for forming a dilute, stable silver nanowire dispersion, with water and low molecular weight alcohols being particularly suitable for forming good dispersions at low concentrations. Where there is a good solvent introduction involved in forming more concentrated dispersions, the introduction solvent should generally be highly soluble or miscible with the initial dispersion solvent, and with respect to the solvent in which PVP is soluble and phase separation of PVP is avoided. Suitable volatile solvents for dispersions include, for example, water, alcohols, glycols, amides, glycol ethers, sufficiently polar aprotic solvents such as dimethyl sulfoxide, some additional polar solvents, and mixtures thereof. Specific volatile solvents include, for example, water, methanol, ethanol, isopropanol, cyclohexanol, ethylene glycol, propylene glycol, dimethyl sulfoxide, ethyl lactate, triethylene glycol, butyl cellosolve, butyl carbitol, dimethylacetamide, dimethylformamide, acetonitrile, and mixtures thereof. In some embodiments, it is preferable to use the above non-volatile solvents. Generally, the solvent includes, in addition to the metal component, some of the residual precursor composition, metal salt anions, polymer components unless some or all of the solvent is a polymer component, and any additives.

[0043] The solvent refers to a liquid composition, and the solvent may be a direct precursor for potential further processing. For example, the solvent may be a monomer, or oligomer, or polymer, which can be polymerized and / or crosslinked by further processing such as heating, irradiation, blending with additional reactants, drying, oxidation, combination thereof, or other suitable approaches. Suitable monomers or oligomers include, for example, acrylic types, such as polyurethane precursors like hydroxyethyl methacrylate, hydroxyethyl acrylamide, tetraethylene glycol, and 1,3-propylenediol; diol or polyol type, epoxy type precursors, such as DGEBA (bisphenol A diglycidyl ether), Celloxide 2021P (Daicel USA, Inc.), or YX8000D (Mitsubishi Chemical Group); radiation-curable liquid adhesives, such as optical adhesive NOA85 (Norland Products, Inc.); and combinations thereof, which can be cured by various thermal, radiation, or chemical means. These polymer precursor solvents may be volatile or non-volatile. These polymer precursor solvents can be blended with the volatile solvents referenced in the paragraph above and will generally be inert under the relevant process conditions.

[0044] In some embodiments, the precursor composition may further include additives such as processing aids. Generally, other processing aids, such as surfactants, thickeners, antioxidants, etc., may or may not be used in various precursor compositions. Generally, any additives will be present in amounts of about 5% by weight or less of the non-volatile components, and in some embodiments, about 0.01% to about 2% by weight. Additives may be selected by composition or amount so as not to significantly impede electrical conductivity.

[0045] As described above, curing refers to the process of converting a precursor composition into a composite material that is solid and conductive. The precursor composition is fluid in the sense that it can be deposited, but the cured material is solid and non-fluid. As described above, curing may generally involve solvent removal by evaporation, polymerization of metal compositions, crosslinkable reduction, combination thereof, or any other process that contributes to the transfer of the precursor to a solid material.

[0046] The properties of cured materials generally depend significantly on the amount and composition of the polymer matrix. For example, the elastic modulus of cured composites is quite strong and can be influenced by these parameters. The composition is generally determined by the precursor composition, but the precise curing process can have some influence on the final composition. In particular, the total metal is carried over from the precursor material, but the reduction of the metal composition during curing can alter the internal morphology relative to the properties of the initial fine particles. In any case, the metal is generally distributed essentially uniformly throughout the composite. The relative amount of metal in the cured composite depends on the total organic components in the cured composite. The total organic contribution to the composite generally includes volatile products resulting from the polymerization or crosslinking reactions of the precursor non-volatile components. From a quantification standpoint, a certain amount of the composite can be heated to a sufficiently high temperature to remove all organic material by heat, leaving only the metal, and the weight loss corresponds to the organic contribution. Such an evaluation can be performed more easily using a calorimeter or a scale and oven.

[0047] Regarding the composition of the cured composite material, the total metal mass may range from an upper limit of about 98 wt%, about 95 wt% in further embodiments, about 92 wt% in some embodiments, about 90 wt% in additional embodiments, and about 85 wt% in some embodiments, to a lower limit of at least about 45 wt% in some embodiments, about 50 wt% in further embodiments, about 55 wt% in additional embodiments, about 60 wt% in other embodiments, and about 65 wt% in some embodiments, based on the upper limit to the lower limit described in any of the above. Depending on the treatment and the presumed presence of reducible metal compositions in the precursors, it may be impossible to quantitatively identify the metal source after curing, although this is evident from the precursor compositions. In general, a reasonable analysis of the composite material should allow for a qualitative assessment of the metal source used in forming the cured composite material. The organic components of the composite material generally include the residual mass of the composite material, but some inorganic by-products may remain from the reducible metal compositions and / or additives. Without knowing the precursor composition, it is not possible to easily quantify the inorganic by-products, which are adjusted to the weight of the metal and are generally less than about 5% by weight of the metal. By-products that are thermally removed together with the organic substance can be considered as part of the weight of the organic substance, and by-products that are not thermally removed together with the organic substance can be considered as part of the weight of the metal. With respect to the cured composite composition, the organic component may be at an upper limit of about 50% by weight, about 45% by weight in a further embodiment, about 42.5% by weight in some embodiments, about 40% by weight in an additional embodiment and about 35% by weight in some embodiments, and at a lower limit of about 2% by weight in some embodiments, about 5% by weight in a further embodiment, about 8% by weight in an additional embodiment, about 10% by weight in other embodiments and about 15% by weight in some embodiments, and is a range based on any of the upper and lower limits described above.

[0048] Method for processing and forming dispersions Advances in silver nanowire dispersion processing have provided the formation of previously unimaginable materials exhibiting remarkable properties that balance novel compositions. With regard to relevant embodiments, the processing procedure is influenced by the adoption of an appropriate method for incorporating the nanowires into the composite material, given the presence of nanowires. To form a good homogeneous material, the silver nanowires can be thoroughly dispersed before being combined with other components of the precursor composition. The applicant has succeeded in dispersing silver nanowires directly in resin as a non-volatile solvent. See application 300 above. Nevertheless, it is preferable to disperse the silver nanowires in a high-boiling point solvent as a stable stock solution, and this approach is illustrated herein. The solvent used in the nanowire dispersion may be selected to be compatible with the polymer precursor. The polymer precursor may or may not be diluted with the volatile solvent, and both versions are illustrated herein. Low-boiling point volatile solvents are not necessarily used unless required as a specific processing aid. In additional or alternative embodiments, some solvents may be removed by evaporation, generally under reduced pressure, to remove some or all of the volatile solvents and produce polymer precursor products. The '300 application teaches suitable solvent introduction procedures for forming concentrated silver nanowire dispersions in a wide range of solvents. In summary, silver nanowires are generally well dispersed in dilute dispersions, generally at about 10% by weight or less in low-boiling point solvents such as ethanol, which are particularly excellent for forming good nanowire dispersions. The desired solvent is then blended with the dilute dispersion in the desired amount, and the low-boiling point solvent is removed by evaporation with vacuum and / or heat. In the example, a 40% by weight solution of silver nanowires was formed in a solvent blend of butyl carbitol (diethylene glycol butyl ether) and triethylene glycol, with the original ethanol solvent removed by a rotary evaporator (rotovap).If desired, and if a low-boiling point solvent is suitable for the polymer resin, a dilute solution is used directly, and then the low-boiling point solvent is removed after blending or during curing.

[0049] Reducible silver compositions have been shown to potentially significantly lower the resistivity of the formed metal composite, providing the ability to reduce metal ions to form in-situ deposited metal and enabling process improvements. The remaining components can be similarly prepared to blend all components together, and this process may vary depending on the properties of the components. Ultimately, a well-mixed composition is generally formed, and the mixing process may vary depending on the concentration and rheology of the composition. Various commercially available mixing devices can be adapted to this process, but shearing should not be excessive, even in the presence of silver nanowires, and sonication can be avoided to prevent damage to the nanowires if it is not desired.

[0050] Polymer precursors can be dissolved in the solvent before being combined with the precursor solution, but liquid polymer precursors can be combined directly. Sonication, grinding, and vortexing can be used to facilitate the dissolution of polymer precursors. The amount of solvent generally varies depending on the properties of the polymer precursor and the solvent, and can be determined by those skilled in the art using additional information, sometimes provided by the supplier. Reducible silver compositions, generally silver salts, can similarly be dissolved before being combined with other components to form a stock solution. Again, the appropriate concentration varies depending on the silver salt and the solvent.

[0051] In some embodiments, in one step of the process, a resin or a resin having a desired amount of solvent can be prepared and combined with metal nanoparticles that do not contain silver nanowires. The combination can then be sonicated and / or mixed in a mechanical mixer to blend the resin and metal nanoparticles. Once the combination is thoroughly mixed, a silver nanowire dispersion is added to the combination, and then the composite precursor material is mixed and / or sonicated to form an ECA precursor material having paste-like properties and ready for coating. If a reducible metal composition is added, silver nanowires may be added before the silver nanowires or after the solvent nanowires for mixing into the composite material. The exemplary processing order can generally be modified with respect to at least some formulations. For example, the resin may be mixed first with silver nanowires and then with other nanoparticles, or the silver nanowires may be mixed with nanoparticles of other materials and then with the resin. Using the teachings herein, a suitable process sequence for a particular formulation can be selected by those skilled in the art.

[0052] As described above, various mechanisms are suitable for crosslinking polymers in composite materials or for removing solvents. Reduction of reducible metal compositions can occur simultaneously with crosslinking, such as when heat treatment is performed. Curing conditions can be adjusted to account for polymer curing and reduction of either metal, and from this, some different conditions, e.g., radiation for polymer curing and heat for silver reduction, as well as the order or potentially simultaneous application of curing conditions, can be empirically selected by those skilled in the art and are generally not expected to be significant to the product. Reduction of reducible metal compositions can also be adjusted, based on the selected chemistry, by the potential inclusion of other reducing agents (which may also be selected based on their reactivity). Heat curing can be carried out by heating to at least about 75°C, and the upper temperature cutoff can be determined by the thermal stability of the polymer, but generally the heating temperature is about 400°C or less. Heating can be carried out from 2 minutes to about 6 hours. Due to the potentially wide range of suitable polymer matrix materials and solvents, a correspondingly wide range of processing conditions is suitable. The presence of a solvent controls the temperature of the material based on the boiling point of the solvent until the solvent evaporates; therefore, thicker deposits may require longer curing times to remove the solvent. In some embodiments, the curing temperature may be about 80 to about 300°C, in further embodiments about 90 to about 250°C, in additional embodiments about 95 to about 225°C, and in other embodiments about 100 to about 200°C. The reduction of silver in the composite materials described herein generally requires longer curing times than those used in thin, transparent conductive systems. In some embodiments, the thermal curing time may be about 3 minutes to about 5 hours, in further embodiments about 5 minutes to about 4 hours, in additional embodiments about 7.5 minutes to about 3 hours, and in other embodiments about 9 minutes to about 2.5 hours. Additional ranges within the specified time and temperature ranges are intended and will be recognized by those skilled in the art as being within this disclosure. Furthermore, laser treatment or higher temperatures exceeding 400°C in an oven, etc., may be useful for further increasing the conductivity of the conductive elements and optionally removing all organic matter.

[0053] In additional or alternative embodiments, when a suitable UV-curable resin is used, curing is performed with ultraviolet light, and UV irradiation may be effective in reducing reducible metal compositions, such as in the presence of ammonia. The transmission of ultraviolet light through metal loading materials can be problematic due to the reflectivity of the metal. This limitation can impose practical constraints on UV curing of thicker composite materials using appropriate radiation doses and appropriate curing times. The actual thickness of UV curing may vary depending on the degree of metal loading and possible supplementation with thermal curing. In some cases, additional heat may be applied before, during, or after UV curing to remove solvents or other volatile substances and further improve the final electrical or thermal conductivity of the conductive elements. The dose of radiation delivered is joules / cm² (J / cm²). 2 UV curing is generally expressed as the energy received per unit area during irradiation time. Suitable light sources can be mercury lamps or UV LED lights. Heating can also occur by irradiation with ultraviolet light, and as a result, thermal curing can occur simultaneously. Commercially available UV curing systems are available from a wide range of suppliers for polymer curing. Pulsed light can be used to provide the desired light, and the intensity of the irradiation can further induce metal sintering, removal of volatile components, and even curing of organic components. Infrared pulsed light can primarily induce curing through the resulting thermal effect. Pulsed light systems are available, for example, from Xenon Corporation (MA, USA) with a range of wavelength options.

[0054] Depending on the desired composition, the precursor composition may exhibit a range of properties, e.g., from printable ink to spreadable paste. The amount of solvent generally provides a versatile, adjustable parameter, while the composition can also be adjusted to modify the properties of the precursor composition. The amount of metal may be selected to a significant degree depending on the target electrical resistivity, and the amount of metal may also constrain the actual range of properties of the precursor and the corresponding deposition options. Nevertheless, a significant range of precursor properties can be provided by reasonable compositional adjustments. While the precursor composition itself may have reasonable electrical conductivity, applications are generally directed towards cured forms that have appropriate stability for application.

[0055] Prior to curing, a precursor composition may be deposited at appropriate locations where the cured composition is intended to provide the desired electrical conductivity. Deposition may include blanket coating and patterning, e.g., laser ablation, photolithography, or other suitable patterning approaches; selective printing, e.g., screen printing, gravure printing, gravure offset printing, nanoimprint printing, etc.; or jetting delivery to directly form the desired conductive structure. Coating methods include, for example, slot coating, spray coating, and extrusion. Generally, commercially available printing or coating equipment can be adapted for the delivery of the precursor composition. More viscous precursors may be delivered by syringe, extrusion, etc. The stereochemistry of the deposited material is highly application-dependent. For example, the deposits may be dots for electrically connecting adjacent elements, e.g., solder balls can be used. In further embodiments, stripes of ECA can be used to electrically connect more distant structures, e.g., to replace metal traces. There are no specific limitations on the particular stereochemistry. The curing conditions are influenced by auxiliary materials, which can limit the process temperature and may be reduced to favor longer process times, thereby regulating the rheology of the ECA precursor and providing a deposition suitable for specific applications.

[0056] Coating / Material Properties Conductive coatings or deposits are generally opaque materials and can be formed for use as non-transparent structures. Non-transparent layers, such as translucent or opaque layers, are generally formed with high metal loading to impart low sheet resistance. With respect to these coatings, cloudiness and other optical properties are generally not a particular concern and may not be significant. These highly conductive structures can be used to form metal traces, busbars, electromagnetic shields, etc. Since electrical conductivity is generally an important characterizing property of composite materials, the amount of silver nanowires can be adjusted based on cost and the desired mechanical properties, as a higher proportion of silver nanowires may increase the mechanical influence from the polymer matrix and decrease metal loading, potentially increasing costs, while a lower proportion of silver nanowires may have the opposite effect.

[0057] The electrical resistance of a thin coating can be expressed as sheet resistance (Rs), and is reported in ohms / square (Ω / □ or Ω / sq) to distinguish it from the bulk electrical resistance value according to parameters related to the measurement process. Sheet resistance along a surface can generally be measured using four-point probe measurement or another suitable process. If the thickness of the structure is known or measurable, the resistivity (ρ) is given by ρ = R s Resistivity is evaluated as t, where t is the average thickness. Resistivity is expressed as R = ρL / A, where ρ is the resistivity, L is the length, and A is the area of ​​the conductive element perpendicular to the direction of conduction. The resistance can be reduced to the extent that the arrangement of busbars or similar arrangement of conductive elements provides a decrease in L or an increase in A. Resistivity is an intrinsic parameter independent of size and has units of ohms-length. While the measured sheet resistance depends on the properties and dimensions of the corresponding structure, resistivity is an intrinsic material property that is independent of structure, assuming the material is uniform. The resistivity of bulk silver is 1.59 × 10⁻⁶. -6 It is reported to be Ω·cm, which is the lower limit of the resistivity of silver-based conductors. Highly loaded silver material has a resistivity of approximately 5 × 10⁻¹⁶. -3 Resistivity of Ω·cm or less, approximately 5 × 10⁻¹⁰ in some embodiments.-4 Ω·cm or less, in further embodiments, about 1×10 -4 Ω·cm or less, in other embodiments about 5×10 -5 ~about 5×10 -6 Ω·cm, as well as any specific resistivity range using any one of the clear lower limit ranges together with the clear upper limit ranges can be achieved. In some embodiments, reduction of a reducible metal composition such as a silver salt can be effective to reduce the confirmed specific resistivity by at least about 25%, in further embodiments at least about 50%, in some embodiments at least about 75%, and in further embodiments it has been found that it can be effective to reduce from about 80% to a measurable value from an open value. It will be recognized by those skilled in the art that further ranges of specific resistivity, and variations in specific resistivity within the above explicit ranges, are contemplated and within the present disclosure.

[0058] For testing, a loaded precursor composition having paste properties was coated onto glass slides between 60 micron thick spacers. The spacers were then removed, and the paste-coated glass slides were cured for a selected time at a selected temperature, such as in a ventilated oven. For UV curable polymers, the prepared glass slides can be exposed to a UV light source at an appropriate dose according to the polymer specification. After curing, the dimensions of the cured ECA coupon can be measured with a micrometer or the like. Also, sheet resistance and resistance can be measured. The measured dimensions, and the measured sheet resistance or resistance, the value of specific resistivity can be calculated. [Examples]

[0059] Materials The following materials were used in Examples 1 to 10: Silver Additive AgFL silver flake, 5~8 microns (47MR-73R, commercially available from Inframat Advanced Materials) AgMP silver nanoparticles, highly uniform spherical silver powder, purity >99%, d50 0.35 microns or average particle size 0.4-1.0 microns (Inframat Advanced Materials) AgNP silver nanoparticles (a) or (b): (a) Silver powder <150nm (Sigma Aldrich) (b) Nanopowder 100nm (SkySpring Nanomaterials) salt AgAc (silver acetate, Ag(O2CCH3)) AgTFA Silver Trifluoroacetate, Ag(O2CCF3)Sigma Aldrich AgHFB (Silver heptafluorobutyrate, Ag(O2CC3F7)) AgLac Silver lactate, Ag(O2CCH(OH)CH3) AgHFA (Silver Hexafluoroantimonate, AgSbF6) Monomers, other organic substances Genomer® 4335, a commercially available trifunctional aliphatic urethane acrylate from Rahn AG, is hydroxy-functional and UV-curable. NOA85 Norland Products, Inc. offers commercially available optical adhesives, aliphatic urethane acrylate and 2,2,2-trifluoroethyl methacrylate (approximately 1:1 by weight), UV curable. V80300 is a commercially available product from Panacol-USA, Inc., called Vitralit® 80300, a modified acrylate. PB3600 is a commercially available product from Daicel ChemTech, Inc., Epolead® PB3600, epoxidized polybutadiene, equivalent to 193 epoxy. Celloxide® 2021P, 3,4-epoxycyclohexyl carboxylate, commercially available from 2021P Diacel ChemTech, Inc., UV or thermosetting. YX8000D is a commercially available product from Mitsubishi Chemical Corp., jER(trademark) YX8000D, a hydrochloride bisphenol A diepoxy, thermosetting. Epon® 815C, a bisphenol A-based epoxy resin, is commercially available from Miller-Stephenson, Inc. + n-butyl glycidyl ether. EX612 Nagase America LLC sells Denacol (trademark) EX-612, sorbitol polyglycidyl ether. MHHPA Hexahydro-4-methylphthalic anhydride HEMA 2-hydroxyethyl methacrylate Imicure® EMI-24, 2-ethyl-4-methylimidazole, and curing agent, commercially available from EMI-24 Evonik Corp.

[0060] H-nanowire HNW Silver nanowires called H-nanoparticles (HNWs) were synthesized in a closed reactor system. A heated reaction solution of ethylene glycol (EG), polyvinylpyrrolidone (commercially available PVP K30 from BASF), and NH4Cl was prepared, followed by the addition of AgNO3 with continuous stirring at approximately 160°C for several hours. After the synthesis was complete, the silver nanowires were purified by acetone precipitation and redispersion in water or other solvents. The purified silver nanowires were removed from the dispersion, dried, and characterized by transmission electron microscopy, for example, as described in U.S. Patent No. 10,714,230 by Hu et al.

[0061] H-nanowires with an average diameter of approximately 60 nm and an average length of approximately 5 microns (referred to as H-5) were prepared. In some examples, H-nanowires with an average length of less than 5 microns were prepared by ultrasonic treatment of H-5 nanowires, reducing their average length to approximately 2 microns and 1 micron, respectively, and are referred to as H-2 and H-1. Unless otherwise specified, H-5 nanowires were used in the examples.

[0062] Manufacturing of HNW composite materials A composite material containing 40% by weight of HNW in epoxy resin was prepared using the following procedure.

[0063] 1. Preparation of HNW stock solution The required amount of HNW in ethanol was placed in a 24 / 40 ground glass Erlenmeyer flask. A solvent mixture of butyl carbitol (BC) and triethylene glycol (TEG) in a weight ratio of 5:1 was added to the flask to obtain an HNW / solvent mixture with a silver-to-solvent weight ratio of 4:6. The HNW / solvent mixture was mixed manually for approximately 1 minute. Ethanol was removed on a rotary evaporator at a water bath temperature set at 35°C. The resulting HNW dispersion concentrate was further dried under vacuum at approximately 60 mmHg at 35-40°C for 4-8 hours to obtain an ethanol-free, 40% by weight HNW dispersion.

[0064] 2. Manufacturing of silver nanoparticles / epoxy resin The curing agent and the epoxy resin mixture containing the curing agent were placed in a 20 mL glass vial. A solvent mixture of BC and TEG in a weight ratio of 5:1 was added to the vial and mixed with the epoxy resin mixture using a vortex mixer for 1 to 3 minutes. Next, the required amount of silver flakes (AgFL) and silver nanoparticles (AgMP) were added to the vial. Mixing was performed for 10 minutes using a THINKY MIXER (Thinky USA) operating at 1000 rpm, followed by sonication for 60 minutes using a BRANSON 8800 Ultrasonic Bath (Branson Ultrasonics Corp.) at 40 kHz.

[0065] 3. Manufacturing of composite materials and coatings The HNW stock solution was added to the silver nanoparticle / epoxy resin, the resulting mixture was vortexed for 1 minute, and then mixed for 10 minutes in a THINKYMIXER operated at 1000 rpm. The resulting paste was then coated onto a microscope glass slide using a 60-micron tape spacer. The coating spacer was then removed, and the coated paste was cured in a well-ventilated box oven at 150°C for 30 minutes. The test coupon was then cooled to room temperature in a ventilated hood, and curing and uniformity were examined.

[0066] The HNW composite materials used in the examples were manufactured in the same manner as described above. For some examples, silver curing was performed using high-intensity pulsed light (IPL) provided by a commercially available system from XENON Corp.

[0067] Test Procedure The length, width, and actual thickness of the cured, uniform coating were measured, and the thickness was measured using a micrometer in various areas of the coupon, with the average being taken as the thickness. A Fluke 1507 multimeter (Fluke Corp.) was used to measure the resistance (R) along the entire length of the coating, and an EXTECH 380460 milliohmmeter (Extech Instruments Co.) was used for sub-ohm resistance values.

[0068] Example 1 - Composite material containing only HNW in urethane acrylate resin Composite materials of HNW in different resin systems were prepared, and UV (18J / cm²) was used. 2 The composites were cured by applying a special agent and then heated at 120°C for 30 minutes. The resistivity of each composite was measured, and the volume resistivity and 25-micron sheet resistance were calculated. The results are shown in Table 1.

[0069] [Table 1]

[0070] Composites of HNW in PB3600 containing EMI-24 crosslinking agent were prepared and cured by heating at 120°C for 30 minutes, followed by 150°C for 5 minutes. The resistivity of each composite was measured, and the 25-micron sheet resistance Rs was calculated. The results are shown in Table 2.

[0071] [Table 2]

[0072] Example 2 - HNW, silver nanoparticles, and AgTFA in urethane-acrylate composite material Composite materials of HNW, silver nanoparticles, and silver salt were prepared as shown in Table 3.

[0073] [Table 3]

[0074] Prepare the composite coating, cure it as described in Table 4, and cure it with UV at 10 J / cm². 2 The process was carried out, followed by further heat treatment. The resistance of each coating after various heat treatments was measured, and the resistivity and sheet resistance Rs were calculated using these measurements. The results are shown in Table 4.

[0075] [Table 4]

[0076] Figure 1 shows a plot of sheet resistance Rs as a function of curing time at 250°C. The sheet resistance decreases significantly up to approximately 4 minutes, and then stabilizes.

[0077] Composite materials S-1 and S-2 were coated and cured at 250°C for a selected time range of 1 to 15 minutes. The resistivity of each coating was measured, and the results are shown in Table 5. Figure 2 is a plot of resistivity as a function of curing time of the coating. The resistivity of the paste before curing was 10 -3 The range was Ω·cm.

[0078] [Table 5]

[0079] Coatings of S-1 and S-2 were prepared on 125-micron PET and 1 mm glass, and cured using IPL. Cross-hatching was formed in the coatings, and adhesion was visually evaluated. Figures 3A-3C show 5x optical microscope images of S-1 (two samples) and S-2 coated on 125-micron PET. All three samples were evaluated according to ASTM Class 5B (ASTM 3359). Figures 4A-4C show 5x optical microscope images of S-1 (two samples) and S-2 coated on 1 mm glass. All three samples were evaluated according to 5B.

[0080] Figures 5 and 6 show 5x magnification images of S-1 coated on 125 micron PET and 1 mm glass, respectively. In each drawing, composite material residue is visible where the cutting lines intersect and on the surface involved in the cutting process. No residue is present between the hatch marks on the surface of either coating, suggesting good adhesion of the composite material to the substrate.

[0081] Composite materials containing HNW and various amounts of silver nanoparticles were manufactured as shown in Table 6. The composite materials were coated onto glass slides and subjected to a 10 J / cm² test. 2 The coatings were UV-cured and then treated at 100°C for 2 minutes. The resistivity of each coating was measured, and the results are also included in Table 6.

[0082] [Table 6]

[0083] The effect of silver flakes alone (without HNW) was evaluated by preparing composite materials using V80300 as the resin shown in Table 7. Composite materials S-10 and S-11 were liquid-coated, and S-12 was paste-coated. The resistance and resistivity of each coating were measured and are shown in Table 8.

[0084] [Table 7]

[0085] [Table 8]

[0086] Example 3 - Curing of urethane-acrylate composite material with pulsed radiation A coating of composite material S-1 was prepared and cured using IPL. The energy / 300 count varied from 300J to 700J.

[0087] [Table 9]

[0088] Figure 7 shows a plot of the resistivity of composite material S-1 as a function of curing energy. When the curing energy increases from 300 J to 700 J after 300 pulses, the resistivity decreases significantly.

[0089] Figures 8A-8C show images of the S-1 cross-section at 10,000x magnification before baking, 20,000x magnification after IPL, and 10,000x magnification after curing at 250°C for 15 minutes, respectively. Compared to the IPL-cured sample, where the morphology of the HNW was altered and not completely melted due to localized thermal processes, the HNW was completely melted in the cured sample. The sample before baking was 1.8 × 10⁻⁶. -2 The sample showed a resistivity of Ω·cm. The sample after IPL measured 1.2 × 10⁻⁶. -4 The sample showed a density of Ω·cm. The hardened sample was 1.6 × 10⁻⁶. -5 It showed Ω·cm.

[0090] Figures 9A and 9B show images of the S-1 cross-section before baking at 10,000x magnification (Figure 9A) and 60,000x magnification (Figure 9B). The HNW is not uniformly dispersed. Conductivity can be improved by improving the dispersion and uniformity of the HNW in the bulk composite.

[0091] Figures 10A and 10B show 350x (Figure 10A) and 20,000x (Figure 10B) images of the S-1 section after IPL (600J / 300ct).

[0092] Figures 11A and 11B show 3000x (Figure 11A) and 10,000x (Figure 11B) images of the S-1 cross section after curing at 250°C for 15 minutes.

[0093] Examples 4-7: HNW in HEMA:G4335 resin This example relates to a composition having a blend of alternative curable polymers. The precursor solution contained HEMA and G4335 as resins in a weight ratio of 7:3. The composition is in the form of: AgFL 2.25g, AgMP 0.75g, AgNW(HNW) 1.0g, resin 1.0g, silver acetate 0.1g (total Ag 2.5%). UV dose 1.8 J / cm² 2 The composite material was called S-13.

[0094] [Table 10]

[0095] The data suggests that 130°C yields better results compared to 150°C. Good hardness and adhesion were confirmed. Figure 12 is a bar graph showing the resistivity for different compositions.

[0096] Example 5 - HNW and silver nanoparticles in epoxy composite material The composite materials shown in Table 11 were prepared using an epoxy resin system.

[0097] [Table 11]

[0098] The reducible silver composition (dissolved in PG / TEG) and reducing agent additives (introduced by addition to the reducible silver composition solution), as shown in Table 12, were added to the composite material. Coatings were prepared using different curing temperatures and times, and their resistivity was measured. The results are shown in Table 12.

[0099] [Table 12]

[0100] The results suggest that S-14 is a better system. AgTFA provided the best resistivity for thermally cured ECA compounded with different resins. S-16 does not appear to be a high-performance system, but the effect of the Ag composition is demonstrated nevertheless. Additional reducing agents did not enhance the effect of the Ag composition.

[0101] Example 6 - Effect of HNW length in epoxy composites Composite materials shown in Table 13 were prepared using an epoxy resin system. The resin mix consisted of Epolead PB3600 150 mg + Denacol EX-612 120 mg + EMI-24 20 mg. 5 mg of PVP was also added as a control in composite material 12d. AgTFA was used with 5% silver relative to total Ag. Both PVP and AgTFA were added in dry powder form and mixed and dissolved with the resin. The AgNP used was a commercially available 100 nm powder from SkySpring Nanomaterials. The results are shown in Table 14.

[0102] [Table 13]

[0103] [Table 14]

[0104] The resistivity was significantly reduced by the use of silver salts. While there was some variation based on the length of the silver nanowires, the trend was not definitive. In particular, when using silver salts, the lowest resistance was found with 2-micron silver nanowires, while without silver salts, 5-micron silver nanowires had the lowest resistivity.

[0105] Example 7 - Effect of different lengths of HNW using processing aids in epoxy formulations In this example, we examined the results obtained with silver nanowires of different lengths using a processing aid. Specifically, thinner (BC) was added as the processing aid. The AgNP and resin mix were the same as in the previous example.

[0106] The composite material compositions and results are shown in Table 15.

[0107] [Table 15]

[0108] Example 8 - Commercially available paste formulation In this example, we consider the use of a reducible silver composition combined with various conductive fine particles.

[0109] Commercial conductive paste made from ACI material S-29: First commercially available conductive paste - Reported composition: Silver 65-85% + Dimethyl glutarate 1-10% S-30: Second commercially available conductive paste - Reported composition: Graphite 40-55% + Carbon Black 10-20% + 2,2-Dimethyl-1,3-Dioxolane-4-ylmethanol 5-10% S-31: Third commercially available conductive paste - Reported composition: Silver 50-70%

[0110] A conductive paste was blade-coated onto a 125um PET sheet and heated as shown in the table. The sheet resistance was measured using a Suragus non-contact resistance meter. The data is summarized in Table 16.

[0111] [Table 16]

[0112] A rectangular coating was applied to a glass slide using a 30-micron spacer, and the same process was followed. The resistance along the entire length was measured, and the volume resistivity was calculated. The results are shown in Table 17. Paste S-29 appeared to exhibit higher resistivity on glass than PET.

[0113] [Table 17]

[0114] A small amount of solvent was used to add a reducible silver composition to a silver-based conductive paste. Only EtOH was found to be compatible with paste S-31 (Table 18). The S-31 composite containing AgTFA / EtOH was coated onto a microscope glass slide using a 30-micron spacer, and the resistance was measured after heating at 120°C for various times. The results are shown in Table 19. Compared to untreated (raw) S-31, AgTFA increased the conductivity by more than 10 times, but the curing time was longer.

[0115] [Table 18]

[0116] [Table 19]

[0117] Example 9 - Effect of AgTFA on resistivity when using UV-curable adhesive Using a vortex mixer, AgFL, AgMP, and optionally AgTFA were mixed with EtOH in a flask, followed by sonication at 40 kHz for 1 hour. The HNW dispersion in EtOH was added to the mixture, and the flask was gently shaken to mix the silver composition. While gently shaking, the monomer resin (V80300) was slowly added to the flask, and the mixture was further mixed with a vortex mixer for 3 minutes. After that, the mixture was heated in a 40°C water bath using a rotary evaporator to remove the ethanol.

[0118] Next, the obtained ECA paste was coated onto a microscope glass slide using a doctor blade technique with a 60 μm tape spacer. After coating, the ECA coupon was UV cured (3.8 J / cm²). 2 Next, it was heated in a well-ventilated box oven at 120°C for 30 minutes, followed by heating at 150°C for another 30 minutes.

[0119] The composition and results are shown in Table 20. The resin was 20% by weight of V80300. The thickness was approximately 40 ± 0.5 microns. Figure 13 shows a bar graph of resistivity as a function of composition.

[0120] [Table 20]

[0121] Example 10 - Thermosetting epoxy formulations containing and not containing a reducible silver composition An EPON 815C epoxy resin system containing 2-ethyl-4-methylimidazole as a curing agent was used.

[0122] The compositions shown in Table 21 were prepared and cured at 150°C for 30 minutes. The results are shown in Table 22. Figure 14 shows a bar graph of resistivity as a function of composition.

[0123] [Table 21]

[0124] [Table 22]

[0125] The embodiments described above are intended to be descriptive and non-restrictive. Further embodiments are within the scope of the claims. Furthermore, while the present invention is described in relation to specific embodiments, it will be recognized by those skilled in the art that modifications may be made in form and detail without departing from the spirit and scope of the invention. Incorporation by reference of the above documents is limited so as not to incorporate subject matter contrary to the express disclosure herein. Unless otherwise specified, the disclosure herein includes specific embodiments, embodiments including specific components, elements, components, or other parts or combinations thereof, and embodiments that essentially consist of such specific components, components, or other parts or combinations thereof, to the extent that specific structures, compositions and / or processes are described herein together with components, elements, components, or other parts, which may include additional features without altering the fundamental nature of the subject matter, as suggested in the discussion. The use of the term “about” herein means an expected uncertainty in the relevant value, as will be understood by those skilled in the art in the specific context.

Claims

1. At least about 2.0% by weight of an organic precursor to form a polymer matrix; Metal particles containing silver flakes and / or silver particles; and Reducible metal compositions; A fluid precursor composition for forming a conductive material, comprising: A fluid precursor composition in which the total metal weight is at least about 45% by weight of the total weight of the composition.

2. The fluid precursor composition according to claim 1, wherein the reducible metal composition is a reducible silver composition.

3. The reducible silver composition is silver acetate (Ag(O 2 CCH 3 )), silver trifluoroacetate (Ag(O 2 CCF 3 )), silver heptafluorobutyrate (Ag(O 2 CC 3 F 7 )), silver lactate (Ag(O 2 CCH(OH)CH 3 )), silver hexafluoroantimonate (AgSbF 6 ), silver fluoride (AgF), silver tetrafluoroborate (AgBF 4 ), silver nitrate (AgNO 3 ), silver perchlorate (AgClO 4 ), silver hexafluorophosphate (AgPF 6 ), or a mixture thereof, The flowable precursor composition according to claim 2.

4. The aforementioned reducible metal composition is silver acetate, silver trifluoroacetate, silver heptafluorobutyrate, silver lactate, silver tetrafluoroborate (AgBF 4 The fluid precursor composition according to claim 2, comprising one or more of silver hexafluorophosphate or silver hexafluoroantimonate.

5. A fluid precursor composition according to any one of claims 2 to 4, comprising about 0.5 to about 40% by weight of silver ions relative to the total weight of metal.

6. The fluid precursor composition according to any one of claims 1 to 5, wherein the metal nanoparticles further comprise silver nanowires.

7. The fluidity precursor composition according to any one of claims 1 to 6, wherein the precursor comprises a (meth)acrylate monomer.

8. The fluidity precursor composition according to any one of claims 1 to 6, wherein the precursor comprises an aliphatic urethane acrylate monomer and an aliphatic (meth)acrylate monomer.

9. The fluidity precursor composition according to any one of claims 1 to 6, wherein the precursor comprises a fluorinated aliphatic (meth)acrylate monomer.

10. The fluid precursor composition according to claim 8, wherein the aliphatic urethane acrylate monomer comprises a monomer having one or more hydroxy-terminated groups, a monomer having one or more epoxy-terminated groups, or a combination thereof.

11. The fluid precursor composition according to claim 8, wherein the aliphatic urethane acrylate monomer comprises a monomer having one or more hydroxyl-terminated groups, and the aliphatic (meth)acrylate monomer comprises a monomer having one or more hydroxyl-terminated groups.

12. The fluidity precursor composition according to any one of claims 1 to 6, wherein the precursor comprises an epoxidized polybutadiene monomer having one or more hydroxy-terminated groups.

13. The fluidity precursor composition according to claim 12, wherein the precursor further comprises an aliphatic ether containing one or more epoxy groups.

14. The fluidity precursor composition according to any one of claims 1 to 6, wherein the precursor comprises an acid anhydride and a monomer having one or more epoxy-terminated groups.

15. The fluid precursor composition according to claim 14, wherein the monomer comprising one or more epoxy-terminated groups is derived from bisphenol A.

16. The fluid precursor composition according to claim 14, wherein the monomer comprising one or more epoxy-terminated groups is derived from hydrogenated bisphenol A.

17. The fluid precursor composition according to any one of claims 1 to 16, wherein the silver flakes have an average particle size of about 1 to 20 microns.

18. The fluid precursor composition according to any one of claims 1 to 17, comprising about 30 to about 50% by weight of the silver flakes based on the total weight of the composition.

19. The fluid precursor composition according to any one of claims 1 to 18, comprising about 30 to about 50% by weight of the silver flakes and about 5 to about 20% by weight of the silver particles, based on the total weight of the composition.

20. The fluid precursor composition according to claim 19, wherein the silver particles have an average particle size of less than approximately 5 microns.

21. The fluid precursor composition according to claim 19, wherein the silver particles have an average particle size of less than about 200 nanometers.

22. The fluid precursor composition according to any one of claims 1 to 21, comprising about 5 to about 80% by weight of silver nanowires and at least about 8.5% by weight of an organic precursor, based on the total weight of the composition.

23. The fluid precursor composition according to claim 22, wherein the silver nanowire has an average length of less than about 10 microns and an aspect ratio of at least about 10.

24. The fluid precursor composition according to any one of claims 1 to 23, wherein the composition comprises about 5 to about 50% by weight of a precursor and at least about 40% by weight of metal fine particles, based on the total weight of the composition.

25. The fluid precursor composition according to any one of claims 1 to 24, comprising at least about 5% by weight of a volatile solvent relative to the total weight of the composition.

26. The fluidity precursor composition according to claim 25, wherein the solvent comprises water, alcohol, glycol, amide, glycol ether, polar aprotic solvent, or a mixture thereof.

27. The fluidity precursor composition according to any one of claims 1 to 26, wherein the precursor is thermosetting.

28. The fluid precursor composition according to any one of claims 1 to 27, wherein the precursor is UV curable.

29. Organic precursors for polymer matrices; and Metal nanoparticles containing silver nanowires and non-nanowire metal nanoparticles; A fluid precursor composition for forming a conductive structure, comprising: A fluid precursor composition wherein the metal nanoparticles contain silver nanowires in an amount of about 5 to about 90% by weight relative to the total weight of the metal nanoparticles.

30. The fluid precursor composition according to claim 29, wherein the metal microparticles that are not nanowires include silver flakes, silver particles, or a blend thereof.

31. The fluid precursor composition according to claim 29 or 30, wherein the metal nanoparticles contain silver nanowires in an amount of about 20 to about 85% by weight relative to the total weight of the metal nanoparticles.

32. The fluid precursor composition according to claim 29 or 30, wherein the metal nanoparticles contain silver nanowires in an amount of about 2 to about 45% by weight relative to the total weight of the metal nanoparticles.

33. The fluid precursor composition according to any one of claims 29 to 32, having a total metal weight of about 50 to about 95% by weight of the total weight of the composition.

34. The fluid precursor composition according to any one of claims 29 to 32, having a total metal weight of about 60 to about 85% by weight relative to the total weight of the composition.

35. The fluidity precursor composition according to any one of claims 29 to 34, wherein the silver nanowire has an average diameter of about 30 nm to about 100 nm and an average length of about 1 to about 100 microns.

36. A fluid precursor composition according to any one of claims 29 to 35, further comprising a reducible metal composition.

37. The said reducible metal composition is silver acetate (Ag(O) 2 CCH 3 )), silver trifluoroacetate (Ag(O 2 CCF 3 )), heptafluorobutyrate silver (Ag(O 2 CC 3 F 7 )), silver lactate (Ag(O 2 CCH(OH)CH 3 )), Silver hexafluoroantimonate (AgSbF 6 ), silver fluoride (AgF), silver tetrafluoroborate (AgBF) 4 ), silver nitrate (AgNO) 3 ), silver perchlorate (AgClO 4 ), silver hexafluorophosphate (AgPF 6 The fluid precursor composition according to claim 36, comprising ), or a mixture thereof.

38. The aforementioned reducible metal composition is silver acetate, silver trifluoroacetate, silver heptafluorobutyrate, silver lactate, silver tetrafluoroborate (AgBF 4 The fluid precursor composition according to claim 36, comprising one or more of silver hexafluorophosphate or silver hexafluoroantimonate.

39. The fluidity precursor composition according to any one of claims 29 to 38, comprising about 0.5 to about 40% by weight of silver ions with respect to the total metal weight of the composition.

40. A fluid precursor composition according to any one of claims 29 to 39, comprising about 5 to about 55% by weight of a precursor.

41. A fluidity precursor composition according to any one of claims 29 to 40, comprising at least about 5% by weight of a volatile solvent.

42. The fluidity precursor composition according to claim 41, wherein the solvent comprises water, alcohol, glycol, amide, glycol ether, polar aprotic solvent, or a mixture thereof.

43. The fluidity precursor composition according to any one of claims 29 to 42, wherein the organic precursor comprises a soluble polymer binder, a crosslinkable or polymerizable monomer, an oligomer or polymer, or a mixture thereof.

44. The fluidity precursor composition according to any one of claims 29 to 42, wherein the precursor comprises a (meth)acrylate monomer.

45. The fluidity precursor composition according to any one of claims 29 to 42, wherein the precursor comprises a monomer having a hydroxyl functional group, a monomer containing an epoxy functional group, a monomer containing an isocyanate functional group, or a mixture thereof.

46. The fluidity precursor composition according to any one of claims 29 to 42, wherein the precursor comprises a fluorinated aliphatic (meth)acrylate monomer, an aliphatic urethane acrylate monomer and an aliphatic (meth)acrylate monomer, an aliphatic urethane acrylate monomer having one or more hydroxyl-terminated groups, an aliphatic urethane acrylate monomer having one or more epoxy-terminated groups, or a mixture thereof.

47. The fluidity precursor composition according to any one of claims 29 to 42, wherein the precursor comprises an aliphatic ether containing one or more epoxy groups; an acid anhydride and a monomer containing one or more epoxy-terminated groups; an acid anhydride and a monomer containing bisphenol A and one or more epoxy-terminated groups; an acid anhydride and a monomer containing hydrogenated bisphenol A and one or more epoxy-terminated groups; or a mixture thereof.

48. The fluidity precursor composition according to any one of claims 29 to 47, wherein the precursor is thermosetting.

49. The fluid precursor composition according to any one of claims 29 to 48, wherein the precursor is UV curable.

50. A conductive composite material comprising a solid polymer matrix and at least about 45% by weight of a metal, wherein the metal is a1) Characteristics of being formed from metal nanoparticles that are not nanowires, and b1) Formed from silver nanowires, formed from deposited metals from a reduced metal composition, A characteristic formed from or both of the above; or a2) Structures formed from silver nanowires, and b2) Deposited metals from reduced metal compositions; A conductive composite material containing [a certain component].

51. The conductive composite material according to claim 50, wherein the solid polymer matrix comprises a chemically crosslinked polymer.

52. The conductive composite material according to claim 50, wherein the solid polymer matrix comprises a physically crosslinked polymer binder.

53. The conductive composite material according to claim 50, wherein the solid polymer matrix comprises a combination of physically crosslinked polymers and chemically crosslinked polymers.

54. The conductive composite material according to any one of claims 50 to 53, wherein the solid polymer matrix comprises an acrylate polymer, a urethane polymer, an epoxy-based polymer, a silicone polymer, or a blend thereof.

55. A conductive composite material according to any one of claims 50 to 54, comprising about 50 to about 95% by weight of metal.

56. A conductive composite material according to any one of claims 50 to 54, comprising about 55 to about 90% by weight of metal.

57. A conductive composite material according to any one of claims 50 to 56, comprising metallic features formed from silver nanowires.

58. A conductive composite material according to any one of claims 50 to 57, comprising metallic features formed from reduced silver ions and not comprising features formed from non-nanowire metal nanoparticles.

59. A conductive composite material according to any one of claims 50 to 57, comprising metallic features formed from reduced silver ions and features formed from non-nanowire metal nanoparticles.

60. A conductive composite material according to any one of claims 50 to 57, comprising features formed from non-nanowire metal nanoparticles and not comprising metallic features formed from reduced silver ions.

61. A conductive composite material according to any one of claims 50 to 56, comprising features formed from non-nanowire metal nanoparticles and metallic features formed from reduced silver ions, but not comprising metallic features formed from silver nanowires.

62. A conductive composite material according to any one of claims 50 to 61, comprising an adhesive polymer.

63. The conductive composite material according to any one of claims 50 to 57 and 59 to 62, wherein the non-nanowire metal fine particles include silver flakes.

64. The conductive composite material according to any one of claims 50 to 57 and 59 to 62, wherein the non-nanowire metal fine particles include silver particles.

65. Approximately 5×10 -3 A conductive composite material according to any one of claims 50 to 64, having an resistivity of Ω·cm or less.

66. Approximately 1×10 -4 ~Approx. 5×10 -6 A conductive composite material according to any one of claims 50 to 64, having an resistivity of Ω·cm.

67. A method for forming a precursor composition for forming a conductive composite material, comprising: A method comprising: a) a polymer matrix precursor comprising a crosslinkable polymer precursor, a polymerizable monomer / oligomer, a soluble polymer binder, or a combination thereof; and b) a metal component provided as two or more of 1) metal nanoparticles other than nanowires, 2) silver nanowires, or 3) a reducible metal composition, wherein the precursor composition contains at least about 45% by weight of the total metal in all forms, and the metal is provided as only silver nanowires and a reducible metal composition, the polymer matrix contains at least 2% by weight of the polymer matrix composition after curing.

68. The method according to claim 67, wherein the silver metal nanowires are dispersed in a dispersant before being combined.

69. The method according to claim 67 or 68, wherein the reducible metal composition is dissolved in a solvent before being combined.

70. The method according to any one of claims 67 to 69, wherein the combining comprises mixing in a mechanical mixer to form a homogeneous precursor composition.

71. The method according to claim 70, wherein the homogeneous precursor composition is fluid.

72. The method according to claim 70 or 71, wherein the homogeneous precursor composition can be deposited by extrusion, spray coating, metering and dispensing, printing, or slot coating.

73. The method according to any one of claims 67 to 72, wherein the precursor composition comprises about 5 to about 55% by weight of a polymer matrix precursor.

74. The method according to any one of claims 67 to 73, further comprising incorporating about 5 to about 45% by weight of a volatile solvent.

75. The method according to claim 74, wherein the solvent comprises water, alcohol, glycol, amide, glycol ether, polar aprotic solvent, or a mixture thereof.

76. The method according to any one of claims 67 to 75, wherein the metal component comprises about 20 to about 80% by weight of silver nanowires.

77. The method according to any one of claims 67 to 76, wherein the metal nanoparticles, other than silver nanowires, include silver flakes.

78. The method according to any one of claims 67 to 77, wherein the metal nanoparticles that are not silver nanowires include silver particles.

79. The method according to any one of claims 67 to 78, wherein the metal component contains about 0.5 to about 40% by weight of silver ions relative to the total weight of the metal and is dissolved in a solvent before being combined.

80. The method according to any one of claims 67 to 79, wherein the precursor of the polymer matrix precursor comprises a (meth)acrylate monomer.

81. The method according to any one of claims 67 to 79, wherein the precursor of the polymer matrix precursor comprises a hydroxyl functional group, an epoxy functional group, a urethane precursor, an epoxy group, a vinyl group, a silicone, or a mixture thereof.

82. The method according to any one of claims 67 to 79, wherein the precursor of the polymer matrix precursor comprises a fluorinated aliphatic (meth)acrylate monomer, an aliphatic urethane acrylate monomer, or a mixture thereof.

83. The method according to any one of claims 67 to 79, wherein the polymer matrix precursor comprises an aliphatic ether containing two or more epoxy-terminated groups; an acid anhydride; an aliphatic monomer containing two or more epoxy-terminated groups; an aliphatic monomer containing two or more epoxy-terminated groups derived from hydrogenated bisphenol A; a hydrogenated bisphenol A monomer containing two or more epoxy-terminated groups; or a mixture thereof.

84. The method according to any one of claims 67 to 83, wherein the precursor of the polymer matrix precursor is thermosetting.

85. The method according to any one of claims 67 to 84, wherein the precursor of the polymer matrix precursor is UV curable.

86. A method for forming a deposit of a precursor material for a conductive composite, comprising depositing the precursor composition formed according to the method described in any one of claims 67 to 85.

87. The method according to claim 86, wherein the cured conductive composite material comprises at least about 8.5% by weight of a polymer matrix.

88. A method for forming a composite material having high electrical conductivity and organic polymer and metal components: A method comprising curing a deposited composition to induce the reduction of silver ions to form a silver metal, wherein the deposited material is a precursor composition comprising a polymer precursor, silver nanoparticles, and a molten silver composition, and the curing comprises applying heat, ultraviolet light, or both for a time sufficient to reduce the silver ions to a silver metal and reduce its resistivity by at least about 25%.

89. The method according to claim 88, wherein the curing includes heating.

90. The method according to claim 89, wherein heating is carried out in an oven at a temperature of approximately 90 to approximately 250°C for 5 minutes to 4 hours.

91. The method according to any one of claims 88 to 90, wherein the organic polymer is crosslinked by heat.

92. The method according to any one of claims 88 to 91, wherein curing includes UV irradiation.

93. The method according to any one of claims 88 to 92, wherein curing includes irradiation using a pulsed light source.

94. The aforementioned silver ions are silver acetate (Ag(O) 2 CCH 3 )), silver trifluoroacetate (Ag(O 2 CCF 3 )), heptafluorobutyrate silver (Ag(O 2 CC 3 F 7 )), silver lactate (Ag(O 2 CCH(OH)CH 3 )), Silver hexafluoroantimonate (AgSbF 6 ), silver fluoride (AgF), silver tetrafluoroborate (AgBF) 4 ), silver nitrate (AgNO) 3 ), silver perchlorate (AgClO 4 ), silver hexafluorophosphate (AgPF 6 The method according to any one of claims 88 to 93, relating to a reducible metal composition comprising, or a mixture thereof.

95. The method according to any one of claims 88 to 94, wherein the deposited composition further comprises a solvent that is removed during curing.

96. The method according to any one of claims 88 to 95, wherein the deposition composition further comprises a reducing agent that promotes the reduction of silver ions during curing.

97. The aforementioned silver ions include silver acetate, silver trifluoroacetate, silver heptafluorobutyrate, and silver tetrafluoroborate (AgBF). 4 The method according to any one of claims 88 to 96, relating to a reducible metal composition comprising one or more of silver lactate, silver hexafluorophosphate, or silver hexafluoroantimonate.

98. The method according to any one of claims 88 to 97, wherein the deposited composition contains about 0.5 to about 40% by weight of silver ions relative to the total weight of the metal.

99. The method according to any one of claims 88 to 98, wherein the deposition composition contains about 5 to about 55% by weight of a polymer precursor.

100. The method according to any one of claims 88 to 99, wherein the deposition composition contains at least about 5% by weight of a volatile solvent.

101. The method according to any one of claims 88 to 100, wherein the deposition composition comprises a precursor of a polymer matrix containing a soluble polymer binder, a crosslinkable or polymerizable monomer, an oligomer or polymer, or a mixture thereof.

102. The method according to claim 101, wherein the precursor of the polymer matrix comprises a (meth)acrylate monomer.

103. The method according to claim 101, wherein the precursor of the polymer matrix comprises a hydroxyl functional group, an epoxy functional group, a urethane precursor, an epoxy group, a vinyl group, a silicone, or a mixture thereof.

104. The method according to claim 101, wherein the precursor of the polymer matrix comprises a fluorinated aliphatic (meth)acrylate monomer, one or more hydroxy-terminated groups, one or more epoxy-terminated groups, or a blend thereof, or a mixture thereof.

105. The method according to claim 101, wherein the precursor of the polymer matrix comprises an aliphatic ether containing two or more epoxy-terminated groups; an acid anhydride and an aliphatic monomer containing two or more epoxy-terminated groups; an aliphatic monomer containing two or more epoxy-terminated groups derived from hydrogenated bisphenol A; a hydrogenated bisphenol A monomer containing two or more epoxy-terminated groups; or a mixture thereof.

106. The method according to any one of claims 88 to 105, further comprising forming the precursor by combining a) a polymer matrix precursor comprising a crosslinkable polymer precursor, a polymerizable monomer / oligomer, a soluble polymer binder, or a combination thereof, and b) a metal component provided as two or more of 1) metal nanoparticles other than nanowires, 2) silver nanowires, or 3) a reducible metal composition, wherein the precursor composition contains at least about 45% by weight of total metal in all forms, and the metal is provided as only silver nanowires and a reducible metal composition, the polymer matrix contains at least 8.5% by weight of the polymer matrix precursor composition after curing.

107. The method according to claim 106, wherein the combining comprises mixing in a mechanical mixer to form a homogeneous precursor composition, and the homogeneous precursor composition is fluid.

108. The method according to any one of claims 88 to 107, wherein the reduction in resistivity is at least about 50%.

109. The resistivity of the aforementioned cured composite composition is approximately 1 × 10 -4 The method according to any one of claims 88 to 108, wherein the value is Ω·cm or less.